2013
DOI: 10.3345/kjp.2013.56.8.332
|View full text |Cite
|
Sign up to set email alerts
|

Early-onset sepsis in a neonatal intensive care unit in Beni Suef, Egypt: bacterial isolates and antibiotic resistance pattern

Abstract: PurposeTo identify the frequency of bacterial isolates in early-onset neonatal sepsis (EONS) and their antimicrobial resistance pattern.MethodsA retrospective study of EONS was conducted at the Beni Suef University Hospital from September 2008 to September 2012. A case of EONS was defined as an infant who had clinical signs of infection or who was born to a mother with risk factors for infection, and in whom blood culture obtained within 72 hours of life grew a bacterial pathogen.ResultsOf 673 neonates screene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
23
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 22 publications
(28 reference statements)
16
23
0
1
Order By: Relevance
“…These differences may be attributed to large sample size (11,790 neonates) compared to our sample size. In agreement with the study of Fahmey, the highest frequency pathogen among culture-proven cases was for Klebsiella that was isolated from 41.5% neonates in our study and 42.8% in the comparative study [14].…”
Section: Discussionsupporting
confidence: 80%
“…These differences may be attributed to large sample size (11,790 neonates) compared to our sample size. In agreement with the study of Fahmey, the highest frequency pathogen among culture-proven cases was for Klebsiella that was isolated from 41.5% neonates in our study and 42.8% in the comparative study [14].…”
Section: Discussionsupporting
confidence: 80%
“…Third generation cephalosporin resistance is now rampant and has been widely reported by recent studies. 3,4,7,8,10,15,16,17 Ceftizoxime revealed better sensitivity pattern against Pseudomonas aeruginosa (57%) in index study when compared to a recent study (25%). 18 Pseudomonas was sensitive to ciprofloxacin in only 47% isolates in our study as against reported sensitivity of 75% by Kumhar. 12 Recent studies reported increased resistance of Pseudomonas to ciprofloxacin varying from 10% to 40.8%.…”
Section: Discussionmentioning
confidence: 67%
“…3 Whereas, many studies reported Klebsiella to be the most common organism. 4,[6][7][8][9] Some authors had found Staphylococcus aureus as the most common organism. 10,11 Intrapartum antibiotic prophylaxis has also led to a substantial change in the bacterial flora responsible for early onset neonatal sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…This prevalence, as well as the finding that S. aureus was the most commonly found Gram-positive bacteria, confirms the findings described by Zaidi et al [25] in their study of neonates with ENS in Latin America, the Caribbean, Asia, and Africa. In Brazil, the study by Paes et al [26] and Silva et al [27], both held in Pará State, also demonstrated a prevalence of Gram-negative bacteria among patients with ENS, which was also observed by Fahmey [28] in India; however, in the latter study, K. pneumoniae was the predominant bacteria found. The study by Sharma et al [29] also demonstrated that S. aureus and E. coli were among the main bacteria found in ENS.…”
Section: Discussionmentioning
confidence: 67%